2019
DOI: 10.3889/oamjms.2019.834
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Mild Cognitive Impairment аmong Apparently Healthy People and the Role of MicroRNAs

Abstract: BACKGROUND: Mild cognitive impairment (MCI) is a stage between the expected cognitive decline of normal ageing and the serious decline of dementia. AIM: To identify risk factors and role of miRNAs associated with mild cognitive impairment (MCI) among employees. SUBJECTS AND METHOD: A cross-sectional study was carried out on 186 employees aged between 40 and 65 years. Cognitive function was evaluated using ACEIII, MoCA, and Quick cognitive tests. Medical history and lifestyle were assessed. Family 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
1
4
2
Order By: Relevance
“…Additionally, miR-874 is transcriptionally controlled by FoxO3a, which is implicated in insulin/insulin-like growth factor signaling with its effect on gene expression, usually in the opposite direction as insulin and IGF-1 [ 36 ]. Similar to the current study, miR-874 expression was not found to be associated with MCI among healthy employee [ 14 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Additionally, miR-874 is transcriptionally controlled by FoxO3a, which is implicated in insulin/insulin-like growth factor signaling with its effect on gene expression, usually in the opposite direction as insulin and IGF-1 [ 36 ]. Similar to the current study, miR-874 expression was not found to be associated with MCI among healthy employee [ 14 ].…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, MCI was detected among 36.2% of T2DM patients, which is much higher than the percrntage of MCI (7.5%) that was reported among healthy employee [ 14 ]. The association of cognitive impairment with T2DM might be related to insulin resistance as insulin receptors are widely distributed throughout the brain.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…miRNAs are small, non-coding RNAs that help regulate gene expression by silencing or activating mRNA transcripts (O'Brien et al, 2018). While there is an extensive evidence demonstrating the mechanistic action of miRNAs in exacerbating obese phenotype (McGregor and Choi, 2011;Mentzel et al, 2015;Iacomino and Siani, 2017), as well as recent evidence in literature demonstrating the role of circulating levels of miRNAs in neurodegenerative disease (Sharma and Lu, 2018;Salama et al, 2019;Yuen et al, 2021). However, there have been limited research that links the underlying mechanisms operant with transcriptional regulation of miRNAs in cognitive decline and neurodegeneration caused by obesity and associated comorbidities.…”
Section: Deckers Et Al 2017mentioning
confidence: 99%
“…In previous studies, several risk factors have been identified for MCI, including educational level, nutrition, older age, hearing impairment, B12 deficiency and active depression in the past 2 years. [ 6 7 8 ] Furthermore, the relationship between oral health status, especially tooth loss, and cognitive impairment has attracted much attention, with tooth loss reported as a factor associated with cognitive impairment or its exacerbation. [ 9 10 11 12 13 14 15 ] Although according to a systematic review, it is unclear how oral health is associated with cognitive status,[ 16 ] hippocampus which is associated with memory, learning and emotions has been shown to be connected with masticatory system via neural circuits.…”
Section: Introductionmentioning
confidence: 99%